Numerical optimization of process parameters in plastic injection molding for minimizing weldlines and clamping force using conformal cooling channel. (April 2018) - Kitayama, Satoshi; Tamada, Kanako; Takano, Masahiro; Aiba, Shuji
Abstract: Weldlines are one of the major defects in plastic injection molding (PIM). Since the weldlines have an influence on not only the appearance of product but also the strength, it is important to reduce the weldlines as much as possible. The melt plastic will be quickly solidified with the low weldline temperature, which results in long weldlines. The weldline temperature is one of the important factors for the weldlines reduction. Clamping force also affect the product quality, but the relationship between the weldlines and the clamping force is rarely discussed in the literature. In this paper, the minimum weldline temperature is maximized for the weldlines reduction, whereas the clamping force is minimized for the high product quality. Therefore, a multi-objective design optimization is performed and the pareto-frontier between them is identified. Numerical simulation in PIM is generally so intensive that a sequential approximate optimization (SAO) using a radial basis function (RBF) network is used to identify the pareto-frontier. Through the numerical simulation, the trade-off between the minimum weldline temperature and the clamping force is clarified.